The agile enterprise : building and running agile organizations - Moreira, Mario E. (Apress, 2017)
Discover how to implement and operate in an Agile manner at every level of your enterprise and at every point from idea to delivery. Learn how Agile-mature organizations adapt nimbly to microchanges in market conditions. Learn cutting-edge practices and concepts as you extend your implementation of Agile through the whole enterprise to meet customer needs. Veteran Agile coach Mario Moreira argues that two critical conditions must be conscientiously cultivated at a company before it can expect to reap in full measure the business benefits of mature Agile. First, individuals at every level must be committed to the mindset and the implementation of practices rigorously focused on delivering value to the customer. Second, all employees must be empowered to take ownership. This holistic transformation wrenches the status quo and provokes a strong focus where customers and employees matter. Readers will learn how to: Establish an idea pipeline to quickly and productively evolve customer value through all levels of the enterprise Incorporate a discovery mindset--experimental, incremental, design, and divergent thinking--and fast feedback loops to increase the odds that what you build aligns more closely to what customer wants Leverage Lean Canvas, personas, story mapping, value stream mapping, Cost of Delay, servant leadership, self-organization, and more to deliver optimum value to customers Use continuous agile budgeting and idea pipelines at the senior levels of the enterprise to enable you to adapt to the speed of the market Reinvent human resources, portfolio management, finance, and many areas of management toward new roles in the enablement of customer value Map a top-to-bottom and end-to-end holistic view of your Agile galaxy to gauge where you are today and where you'd like to go in your Agile future Be truly Agile throughout your enterprise, focused on customer value and employees above all else.